INCREASING STUDENT LEARNING ACHIEVEMENT IN ENGLISH SUBJECTS USING THE GROUP INVESTIGATION METHOD IN CLASS VII UPTD SMP NEGERI 6 SINJAI - Sinar, Sinar (Publikasi dan UKI Press UKI Toraja., 2022)
The method is suitable and considered succeed in increase achievement study English lessons with use Group Investigation method. In study this researcher uses technique data collection carried out in a manner qualitative obtained from observation at the time ongoing learning process teach During research, and methods quantitative obtained from test results study subject on each cycle. Then the data is analyzed in a manner qualitative, that is explain Action results during the learning process teach, and in quantitative with use statistics descriptive that is average score, table frequency, value minimum, value maximum, distribution table and table presentation